Jawabanmu

2014-06-14T20:09:48+07:00
    Ca(OH)2 + 2HCOOH ⇒ Ca(HCOO-)2 + 2H2O
m     20            50                 -                  -
r       20            40                  20              40    -
s      -               10mmol         20mmol

Ca(HCOO-)2 ⇒ Ca2+ + 2 HCOO-
       20              20          40
H+ = Ka (asam lemah/Basa konjugasi)
      =10^-4 (10/40) = 0,25 x 10^-4 = 2,5 x 10^-5

pH = 5 -log 2,5
2014-06-14T20:20:15+07:00
Mol Ca(OH)₂ = 200ml x 0,1 M
                    = 20 mmol
mol HCOOH = 100ml x 0,5M
                   = 50mmol 
 
   Ca(OH)₂ + 2HCOOH -----> (HCOO)₂Ca + 2H₂O
m : 20mmol    50mmol
r :  20mmol     40mmol
s:      -            10mmol          20mmol          40mmol

[H⁺] = ka x  \frac{mol asam}{mol garam}
[H⁺] = 1x10⁻⁴ x  \frac{10}{20}
[H⁺] = 5 x 10⁻⁵

pH = -log[H⁺]
pH = -log[5x10⁻⁵]
pH = 5